Permafrost Dynamics Observatory: 3. Remote Sensing Big Data for the Active Layer, Soil Moisture, and Greening and Browning - Elizabeth Wig; Kevin Schaefer; Roger Michaelides; Richard Chen; Leah K. Clayton; Brittany Fager; Lingcao Huang; Andrew D. Parsekian; Howard Zebker; Yingtong Zhang; Yuhuan Zhao (Earth and Space Science)
Abstract Because of the remote nature of permafrost, it is difficult to collect data over large geographic regions using ground surveys. Remote sensing enables us to study permafrost at high resolution and over large areas. The Arctic‐Boreal Vulnerability Experiment's Permafrost Dynamics Observatory (PDO) contains data about permafrost subsidence, active layer thickness (ALT), soil water content, and water table depth, derived from airborne radar measurements at 66 image swaths in 2017. With nearly 58,000,000 pixels available for analysis, this data set enables new discoveries and can corroborate findings from previous studies across the Arctic‐Boreal region. We analyze the distributions of these variables and use a space‐for‐time substitution to enable interpretation of the effects of climate trends. Higher soil volumetric water content (VWC) is associated with lower ALT and subsidence, suggesting that Arctic soil may become drier as the climate warms. Soil VWC is bimodal, with saturated soil occurring more commonly in burned areas, while unburned areas are more commonly unsaturated. All permafrost variables show statistically significant differences from one land cover type to another; in particular, cropland has thicker active layers and developed land has lower seasonal subsidence than most other land cover types, potentially related to disturbance and permafrost thaw. While vegetation browning is not strongly associated with any of the measured permafrost variables, more greening is associated with less subsidence and ALT and with higher bulk soil VWC.